2001
DOI: 10.1016/s1010-7940(01)00842-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition in patients undergoing cardiopulmonary bypass surgery is associated with an increase of inflammatory cytokines

Abstract: The presence of the E4 allele is associated with increased release of IL-8 and TNF-alpha after CBP surgery. The preoperative determination of E4 in patients undergoing cardiac surgery may lead to additional perioperative measures for the treatment of an increased systemic inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
4
23
0
Order By: Relevance
“…Two studies have shown that carriers of the APO⑀4 allele have an increased inflammatory response to cardiopulmonary bypass (22,46), which may explain the increase in neurologic morbidity in this patient population (47). apoE may also play a particularly important role in mediating the inflammatory response to central nervous system injury (17,36), consistent with clinical observations associating the APO⑀4 allele with poor neurologic outcomes in patients with a variety of acute traumatic and ischemic brain injuries (21,48,49).…”
Section: Discussionsupporting
confidence: 57%
“…Two studies have shown that carriers of the APO⑀4 allele have an increased inflammatory response to cardiopulmonary bypass (22,46), which may explain the increase in neurologic morbidity in this patient population (47). apoE may also play a particularly important role in mediating the inflammatory response to central nervous system injury (17,36), consistent with clinical observations associating the APO⑀4 allele with poor neurologic outcomes in patients with a variety of acute traumatic and ischemic brain injuries (21,48,49).…”
Section: Discussionsupporting
confidence: 57%
“…Nevertheless, limited data in humans show an effect of apoE genotype on pro-and anti-inflammatory cytokines independently of any exogenous source of experimental inflammation inducer. In a study of patients undergoing cardiopulmonary bypass surgery, a process that induces a transient rise in pro-inflammatory cytokines mainly released by activated monocytes, it was shown that apoE4 was associated with increased IL8 and TNFa [82]. In patients with acute coronary syndrome, significant lower levels of the anti-inflammatory IL10 were observed in e4 carriers, with the same trend evident in chronic stable angina patients [83].…”
Section: Inflammation In Relation To Cvdmentioning
confidence: 97%
“…To date, studies examining associations between surgery and delirium have investigated microemboli migration [149][150][151], hypoperfusion [64,137,[152][153][154], inflammatory responses [155][156][157], changes in hormone levels [158][159][160][161], and local and general anesthesia [64,133,162,163]. Gottesman and colleagues [152] hypothesized that a drop in the mean arterial pressure may put patients at risk for early cognitive dysfunction.…”
Section: Surgical Factors and Postoperative Cognitive Dysfunctionmentioning
confidence: 99%